2021
DOI: 10.22146/agritech.55328
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Fisiko-kimia , Organoleptik, dan Kandungan Gizi Mayones Minyak Buah Merah (Pandanus conoideus)

Abstract: Mayones adalah produk berbasis minyak dalam bentuk emulsi minyak semi-padat dalam air (o/w). Penggunaan berbagai jenis minyak dapat mempengaruhi sifat fisikokimia dan penerimaan dari mayones. Penelitian ini bertujuan untuk menentukan tingkat penerimaan panelis terhadap mayones yang terbuat dari beberapa jenis minyak yaitu minyak buah merah kasar (MBMK), minyak buah merah hasil degumming (MBMD), minyak wijen dan minyak sawit (sebagai pembanding), karakteristik fisikokimia dan organoleptiknya, serta kandungan gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 2 publications
0
8
1
2
Order By: Relevance
“…The previous research, the crude RFO mayonnaise was found stable for 3 days when the crude RFO level was at 35% (Sarungallo et al,2021). The present research tried to improve crude RFO mayonnaise with better colour and emulsion stability by lowering the crude RFO to 10-25%.…”
Section: Physical Properties Of Crude Rfo Mayonnaisementioning
confidence: 75%
See 3 more Smart Citations
“…The previous research, the crude RFO mayonnaise was found stable for 3 days when the crude RFO level was at 35% (Sarungallo et al,2021). The present research tried to improve crude RFO mayonnaise with better colour and emulsion stability by lowering the crude RFO to 10-25%.…”
Section: Physical Properties Of Crude Rfo Mayonnaisementioning
confidence: 75%
“…Mayonnaise making method was according to Sarungallo et al, (2021) with minor modification during homogenization steps. The compositions of all formulas are presented in Table 1.…”
Section: Mayonnaise Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The higher egg yolk replacement by of OSAcorn starch concomitantly with the increased corn starch addition contributed to the significant lowering fat content. In comparison to mayonnaise of red fruit oil which consists of 73.60% (db) fat and 46.50% (wb) moisture content (Sarungallo et al, 2021) as well as Indonesian National Standard which rules out the minimum fat content of mayonnaise at least 65% (BSN, 1998), the present research succeeded to reduce significant amount of fat. All of the mayonnaise samples used OSA corn starch to substitute the egg yolk and the addition of corn starch, including the addition of the same quantity of palm oil (2.5 g), resulted in less fat content than the commercial common mayonnaise.…”
Section: Fat Contentmentioning
confidence: 86%